2006
DOI: 10.1152/physrev.00039.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling and Exocytosis in Adrenal Chromaffin Cells

Abstract: At a given cytosolic domain of a chromaffin cell, the rate and amplitude of the Ca2+ concentration ([Ca2+]c) depends on at least four efficient regulatory systems: 1) plasmalemmal calcium channels, 2) endoplasmic reticulum, 3) mitochondria, and 4) chromaffin vesicles. Different mammalian species express different levels of the L, N, P/Q, and R subtypes of high-voltage-activated calcium channels; in bovine and humans, P/Q channels predominate, whereas in felines and murine species, L-type channels predominate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
307
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(324 citation statements)
references
References 410 publications
(581 reference statements)
15
307
1
1
Order By: Relevance
“…100 µM PFOS not only markedly enhanced ICa but also caused a clear left-shift of the curve ( Figure 3D, P < 0.001, two-way ANOVA). VDCCs are involved in various neuronal functions, among which the L-type has been widely studied (19). To further characterize the PFOS effect on calcium channel subtypes, nifedipine was added to the bath solutions during current recordings.…”
Section: Paired T-test)mentioning
confidence: 99%
“…100 µM PFOS not only markedly enhanced ICa but also caused a clear left-shift of the curve ( Figure 3D, P < 0.001, two-way ANOVA). VDCCs are involved in various neuronal functions, among which the L-type has been widely studied (19). To further characterize the PFOS effect on calcium channel subtypes, nifedipine was added to the bath solutions during current recordings.…”
Section: Paired T-test)mentioning
confidence: 99%
“…Of particular relevance is whether T-type channels are capable of coupling to secretion and preserve their characteristic low-threshold of activation. In addition, it is interesting to assay how close the secretory events follow the voltage-dependence of Ttype channels and how T-type channels may coexist with the other voltage-gated Ca 2+ channels normally expressed in rodent chromaYn cells, in particular with the L-type channels which are the dominant Ca 2+ channel subtypes controlling secretion in these cells (see Garcia et al 2006). Besides being the most densely expressed Ca 2+ channels in rodent chromaYn cells, L-type channels possess other important features: (1) control 30% of catecholamine release in in-vivo perfused rat adrenal glands while P/Q and N-type channels contribute marginally (Akiyama et al 2004), (2) can be up-and down-modulated by -adrenergic autoreceptors (Hernandez-Guijo et al 1999;Cesetti et al 2003) and aVected by phosphodiesterase type-4 activity , (3) contribute to a lowthreshold "pace-maker" current that sets the action potentials autorythmicity at rest (Carbone et al 2006c).…”
Section: Introductionmentioning
confidence: 99%
“…According to the initial formulation, stimulus promotes Ca 2+ entry, which increases the cytosolic Ca 2+ concentration ([Ca 2+ ] C ) and triggers exocytosis [20,21]. Later studies showed that the genesis of the [Ca 2+ ] C signal includes subtle nuances contributed by the intracellular Ca 2+ -handling organelles [5,8,24,25]. To begin with, Ca 2+ entering through the plasma membrane Ca 2+ channels is buffered by cytosolic Ca 2+ buffers, so that the increase of [Ca 2+ ] C is much less than expected.…”
Section: Introductionmentioning
confidence: 99%
“…In this way high [Ca 2+ ] C microdomains (HCMD) are built at the secretion site whereas [Ca 2+ ] C near the resting level is preserved at the cell core. Mitochondria play a prominent role in shaping the [Ca 2+ ] C signal in chromaffin cells [24]. On the other hand, changes of Ca 2+ concentration in the mitochondrial matrix ([Ca 2+ ] M ) modify the rate of respiration [27,32,47,49,51] and, when excessive, can trigger cell death [22].…”
Section: Introductionmentioning
confidence: 99%